Actin grips: Circular actin-rich cytoskeletal structures that mediate the wrapping of polymeric microfibers by endothelial cells. (June 2015) - Jones, Desiree; Park, DoYoung; Anghelina, Mirela; Pécot, Thierry; Machiraju, Raghu; Xue, Ruipeng; Lannutti, John J.; Thomas, Jessica; Cole, Sara L.; Moldovan, Leni; Moldovan, Nicanor I.
Abstract: Interaction of endothelial-lineage cells with three-dimensional substrates was much less studied than that with flat culture surfaces. We investigated the in vitro attachment of both mature endothelial cells (ECs) and of less differentiated EC colony-forming cells to poly-ε-capro-lactone (PCL) fibers with diameters in 5–20 μm range ('scaffold microfibers', SMFs). We found that notwithstanding the poor intrinsic adhesiveness to PCL, both cell types completely wrapped the SMFs after long-term cultivation, thus attaining a cylindrical morphology. In this system, both EC types grew vigorously for more than a week and became increasingly more differentiated, as shown by multiplexed gene expression. Three-dimensional reconstructions from multiphoton confocal microscopy images using custom software showed that the filamentous (F) actin bundles took a conspicuous ring-like organization around the SMFs. Unlike the classical F-actin-containing stress fibers, these rings were not associated with either focal adhesions or intermediate filaments. We also demonstrated that plasma membrane boundaries adjacent to these circular cytoskeletal structures were tightly yet dynamically apposed to the SMFs, for which reason we suggest to call them 'actin grips'. In conclusion, we describe a particular form of F-actin assembly with relevance for cytoskeletal organization in response to biomaterials, for endothelial-specific cell behavior in vitro and in vivo, and for tissue engineering.